ANALISIS ALIRAN PANAS DI KONDENSOR DAN EVAPORATOR PADA SISTEM PENDINGIN WATER CHILLER MENGGUNAKAN VARIASI SUHU DENGAN METODE LMTD - Setyo Budi Santoso; Effendi Mohammad (ELEMEN : JURNAL TEKNIK MESIN, 2023)
As a producer of cold water in large quantities used by PT. XYZ Pasuruan to cool the room and production machines, one of the most important elements is to use a water chiller system. Success in producing cold water is supported by optimal parameter settings in the system. Less than optimal settings result in a decrease in the COP value of the water chiller system.This research was conducted to analyze the heat flow in the condenser and evaporator using temperature variations in the water chiller system. Data processing was carried out using the Logarithmic Mean Temperature Difference (LMTD) method From the results of research using temperature variations, the optimal settings for the water chiller system were obtained, namely at a temperature variation of 5⁰C with a COP of 6.1 and an LMTD value of 3.97 for the condenser and 1.49 for the evaporator.